2013
DOI: 10.1179/1743132813y.0000000230
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of TCD for intracranial arterial stenosis/occlusion in patients with acute ischemic stroke: the importance of time interval between detection of TCD and CTA

Abstract: Transcranial doppler shows high diagnostic accuracy against CTA if both are performed in a short time interval in evaluating intracranial arterial stenosis/occlusion in patients with AIS, especially for MCA obstruction. Transcranial doppler can also provide additional real-time dynamic findings complementary to the information provided by CTA. This can result in changes in the management in some of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Therefore, the results of our study using TCD ultrasonography could have more reliability according to the results of the previous study regarding the usage of TCD for diagnosing ICAS. 15 In addition, greatest advantage of TCD in the setting like our study is the noninvasive character of the method without any radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the results of our study using TCD ultrasonography could have more reliability according to the results of the previous study regarding the usage of TCD for diagnosing ICAS. 15 In addition, greatest advantage of TCD in the setting like our study is the noninvasive character of the method without any radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study performed in Chinese patients, the authors prospectively compared the diagnostic accuracy of TCD ultrasonography as an additional screening tool for ICAS with that of computed tomographic angiography in patients with acute ischemic stroke. 15 They found that TCD ultrasonography demonstrated higher diagnostic accuracy than computed tomographic angiography, especially for middle cerebral artery, suggesting that TCD ultrasonography could be an alternative diagnostic tool to detect ICAS. Therefore, the results of our study using TCD ultrasonography could have more reliability according to the results of the previous study regarding the usage of TCD for diagnosing ICAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examination results indicate that TCD and CTA have good consistency in the detection of intracranial stenosis, especially in the case of MCA, and the results are consistent with those in Guan Jingxia's research. [17] In this paper, the statistical analysis results show that the rate of compliance is lower than that of the anterior circulation, which is related to the anatomical structure of vertebral artery and basilar artery. All the cases in our research were diagnosed as LAA, which carries higher incidence rate of vascular stenosis as well as detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…33 CTA is considered the gold standard when evaluating TCD for occlusion detection. TCD is only able to detect skull base/proximal occlusions and has limited accuracy 34 when compared with CTA as the gold standard 35 but can be complementary to CTA in the acute setting given the dynamic nature of stroke where changes in occlusion status can occur quickly. 36,37 With the advent of endovascular treatment, there has been increasing attention given to understanding recanalization rates with treatments, such as intravenous thrombolysis, to determine when endovascular treatment is necessary.…”
Section: Occlusion Detection and Thrombus Lengthmentioning
confidence: 99%